2011
DOI: 10.1177/155892501100600204
|View full text |Cite
|
Sign up to set email alerts
|

On the Pressure Behavior of Tubular Weft Knitted Fabrics Constructed from Textured Polyester Yarns

Abstract: This study attempts to investigate the pressure behavior of tubular knitted fabrics after a long period of time. For this purpose, two kinds of knitted fabric (plain and interlock) with various stitch lengths were chosen and the interfacial pressure and pressure reduction of fabrics after 48 hours were analyzed at different strain percents. The same tests were performed on the same specimens after repeated washing and repeated usage. Finally, the experimental pressure values were compared with the theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Since clothing pressure largely depended on its biaxial extension and stress relaxation properties [81], research studies have been conducted to find the relationship between the clothing pressure of knitted fabrics and stress under extension and recovery processes [82,83]. The pressure behavior of tubular knitted elastic fabrics at different extension levels during 48 hours was investigated and it was found that the stitch length and extension rate are the vital factors that affects the interfacial pressure and pressure reduction [84]. The effects of spandex feeding rate and the fabric structure of elastic fabric were also analyzed [85].…”
Section: Fabric Construction and Mechanical Propertiesmentioning
confidence: 99%
“…Since clothing pressure largely depended on its biaxial extension and stress relaxation properties [81], research studies have been conducted to find the relationship between the clothing pressure of knitted fabrics and stress under extension and recovery processes [82,83]. The pressure behavior of tubular knitted elastic fabrics at different extension levels during 48 hours was investigated and it was found that the stitch length and extension rate are the vital factors that affects the interfacial pressure and pressure reduction [84]. The effects of spandex feeding rate and the fabric structure of elastic fabric were also analyzed [85].…”
Section: Fabric Construction and Mechanical Propertiesmentioning
confidence: 99%
“…Maleki et al. [15] have observed the pressure behavior of tubular knitted fabrics (plain and interlock) with various stitch lengths (0.22, 0.25, 0.29 and 0.32 cm) after a long period of time. The pressure reduction of the fabrics was analyzed after 48 h at the different strain percent (10%, 20% and 25%).…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting the raw fibre, yarn and knit structure can produce stockings of varying compression. Maleki et al [428] investigated the influence of stitch length, strain, washing operation and repeated usage on the pressure behaviour of knitted fabrics; all of which are important factors for the stocking. Further studies have demonstrated that the elastane yarn count is the most effective parameter affecting pressure characteristics [429] and that the tensile energy, tensile strain, shearing stiffness and bending rigidity are all key mechanical properties for compression stockings [430].…”
Section: Stasis Of Blood Flowmentioning
confidence: 99%